Gambaran Adiksi, Pola Asuh, dan Attachment Style pada Mantan Pecandu Sabu-Sabu di Kota X - Kudadiri, Della Hotna Mulia Nola (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The purpose of this study is to explore and understand the experiences of former methamphetamine addicts in rehabilitation centers. The method used method used is qualitative with a case study approach. Subject A who is 28 years old and is undergoing the rehabilitation process in one of the rehabilitation houses in X City participated as a subject. Data collection over five weeks involved interviews and observations. Data analysis involved data reduction, presentation, and conclusion drawing, with validity checks using triangulation. Interviews revealed psychological dynamics, avoidant attachment style, and permissive-indulgent parenting. Subject shared his journey of addiction to methamphetamine, including emotional changes, antisocial behavior, and the impact on his family relationships. This study provides an understanding of the experiences of former methamphetamine addicts and can help design rehabilitation programs that are more suited to individual characteristics, especially for those with avoidant attachment style